Pengaruh Atribut Produk dan Harga Terhadap Keputusan Pembelian Smartphone Oppo pada Mahasiswa Fakultas Ekonomi Universitas Hasyim Asy’ari Jombang - Anggriani Anggriani (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2019)
This research as a purpose to know the influence of produce attribute and the price of buying decision of oppo smartphone to students of economic faculty of Hasyim Asy’ari University. The kind of this research was quantitative research descriptive associative. The population of this research was the students of economic faculty who was used oppo smartphone number 178 people. The technique of sample decision used purposive sampling with much number sample 123 people. The technique of data analyse used validity and reliability, classic assumption test, and hypothesis test. The result showed: (1) The product attribute had positive influential to buying decision of oppo smartphone to student management faculty of Hasyim Asy’ari university Jombang. (2) the price had positive influential of buying decision of oppo smartphone to student management faculty of Hasyim Asy’ari University Jombang. (3) The product attribute and the price simultaneously had positive influential of buying decision of oppo smartphone to students management faculty of Hasyim Asy’ari University.